The Autonomic-Cognition Clinical Correlation in Indonesian Parkinson’s Disease Subjects - Jody, Abraham Al; Tiksnadi, Amanda; Hildaria, Margareth; Asmoro, Anastasia; Candra, Putri Nabilah; Tunjungsari, Dyah (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2024)
Background: Dysautonomia and cognitive impairment are common in PD, affecting quality of life and disease progression. Understanding their connection enables earlier identification of at-risk patients. This study investigates the correlation between dysautonomia and cognitive impairment in Indonesian PD patients. Methods and Materials: This cross-sectional study collected demographic and clinical data, including SCOPA-COG INA and SCOPA-AUT INA. Independent t-tests, Mann-Whitney U tests, Pearson’s, and Spearman’s correlation tests analyzed associations. Results: We recruited 33 PD subjects, primarily male (72.7%) and elderly (63.6%). The median age was 61 years, with 60.6% having a disease duration of at least 5 years and 66.7% at a mild stage. Median levodopa equivalent daily dose (LEDD) was 325 mg. Median SCOPA-COG INA and SCOPA-AUT INA were 24 and 17. Cognitive impairment was present in 45.4%, and dysautonomia in 15.2%. Elderly subjects had lower SCOPA-COG INA (20.19±7.18 vs 27.58±5.98). Cognitively impaired subjects had worse SCOPA-AUT INA (20.6±7.81 vs. 13.89±6.43) and higher LEDD (408.33±140.25 vs. 275.28±134.51). Cognitively impaired subjects had worse SCOPA-AUT INA urinary symptoms (p<0.05). No differences were found between subjects with and without dysautonomia or when divided by median SCOPA-AUT INA. SCOPA-COG INA and SCOPA-AUT INA were significantly correlated (ρ = -0.368, p < 0.05), as were the SCOPA-COG INA memory domain and SCOPA-AUT INA cardiovascular domain (ρ = 0.399, p < 0.05). Conclusion: In Indonesian PD patients, cognitive impairment is significantly correlated with dysautonomia. Age, age at onset, and LEDD were significantly associated with cognitive impairment but not with dysautonomia. Further exploration could enhance understanding of this correlation.